(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Yuliadhi KA, Supartha IW, Wijaya IN, Pudjianto, Nurmansyah A, Susila IW, Yudha IKW, Utama IWEK, Wiradana PA. 2021. Short communication: The preference and functional response of Sycanus aurantiacus (Hemiptera: Heteroptera: Reduviidae) on three prey types in laboratory conditions. Biodiversitas 22: 5662-5667. Sycanus aurantiacus Ishikawa et Okajima (Hemiptera: Heteroptera) is a valuable predatory insect that can be cultivated in biological pest control programs, particularly in vegetable crops. The research aimed to investigate the preferences and functional responses of the predator Sycanus aurantiacus to three different prey species in the laboratory conditions, included Plutella xylostella (Linnaeus), Crocidolomia pavonana (Fabricius), and Tenebrio molitor (Linnaeus). The preference experiment was carried out by monitoring the prey on which S. aurantiacus preyed the most. The functional responsiveness of S. aurantiacus was determined by measuring the time it took to detect and prey on various kinds of prey, as well as the number of prey that were successfully preyed upon when the quantity of prey was increased. The predatory S. aurantiacus preferred P. xylostella over C. pavonana and T. molitor. S. aurantiacus functional response to three kinds of prey, including type II, is shown. In P. xylostella, the instantaneous prey search rate (a) was 0.2/hour, with a handling time (Th) of 1 hour 40 minutes/prey, which was quicker than the other two kinds of prey. As a result of our findings, the predator S. aurantiacus can be maintained in the lab and has the potential to be developed as an efficient biocontrol agent, particularly against the cabbage leaf caterpillar P. xylostella.